Cash to Cashless - A Paradigm Switch - Nichani, Soumya (SFIMAR Research Review, 2018)
The Indian economy is largely a cash-driven economy with less than 5 per cent of all payments happening electronically. As per RBI Annual Report of 2016-17 the currency in circulation at end-March 2017 was 8.8 per cent of GDP,' down from 12.2 per cent in the previous year. Experts believe that high cash to GDP ratio is the biggest impediment in India's march towards becoming a cashless economy. Many reports indicate that India is among the largest users of cash in the world. A study by Nomura Global research in May showed that cash-to-GDP ratio has jumped back to the pre-demonetisation level of about 11.3 per cent on April 27, 2019 which is nearly close to pre-demonetisation levels. Apart from the much-talked about benefits of a low cash economy, there is also another side in the shift to a cashless society. The rationale for pushing for cash-less society is having a paper trail for transactions thereby decreasing crime, money laundering, and tax evasion. One mustn't ignore the way this could potentially empower central banking system to have more power in modifying the way people save and spend money. This may lead to policy options such as negative interest rates as a disincentive to save and encourage consumer spending. There are many challenges in the road ahead like inadequate telecom infrastructure, low rural mobile penetration, large informal labour force, cyber security compromises and high levels of tax evasion. While an Indian 'Cashless' society may definitely seem utopian, a LESS-CASH society seems achievable in the short-term.